1996
DOI: 10.1093/oxfordjournals.humrep.a019513
|View full text |Cite
|
Sign up to set email alerts
|

Infertility: Prognostic indicators for intrauterine insemination (IUI): statistical model for IUI success

Abstract: A retrospective analysis of 260 completed intrauterine insemination (IUI) cycles was used in an attempt to identify significant variables predictive of treatment success. Couples received a maximum of three IUI cycles for the treatment of anovulation, cervical factors or unexplained infertility. Male factor problems were largely excluded by pretreatment screening. The overall pregnancy rate was 19.6% per completed cycle, the miscarriage rate 15.6%, the multiple pregnancy rate 23.5% and the cancellation rate 19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
84
5
11

Year Published

1999
1999
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(114 citation statements)
references
References 0 publications
14
84
5
11
Order By: Relevance
“…The advancing maternal age decreases female fecundity 13 and this is due to reduced uterine receptivity 14 and/ or decreased oocyte quality. However, the prognostic value of woman's age was not significant in studies undertaken by Brzechffa et al 15 and Tomlinson et al 16 which was similar to our study.…”
Section: Koli P Et Al Int J Reprod Contracept Obstet Gynecol 2013 Ssupporting
confidence: 92%
“…The advancing maternal age decreases female fecundity 13 and this is due to reduced uterine receptivity 14 and/ or decreased oocyte quality. However, the prognostic value of woman's age was not significant in studies undertaken by Brzechffa et al 15 and Tomlinson et al 16 which was similar to our study.…”
Section: Koli P Et Al Int J Reprod Contracept Obstet Gynecol 2013 Ssupporting
confidence: 92%
“…In the present study, we also observed that as the infertility duration became longer, the gestation rates also increased. However, in the literature, many studies have indicated that as the age (5,8,17) and infertility duration (7,17,18) increase, gestational rates decrease. Also, Ibérico et al (19) reported in a study published in 2004 that gestational rates in IUI decreased independently of the age through longer infertility durations.…”
Section: Discussionmentioning
confidence: 99%
“…Studies evaluating prognostic indicators for success in IUI cycles have indicated that duration of infertility is an important prognostic indicator. 11 The mean duration of infertility varied significantly between the pregnant and the non pregnant group (p value = 0.049). FSH levels greater than 10 IU/L have high specificity(80-100%) for predicting poor response to stimulation, but their sensitivity to identify such women is low and decreases with threshold value.…”
Section: Discussionmentioning
confidence: 95%